TOURIST MOTIVATION TO VISIT THE PANCORAN SOLAS TOURISM DESTINATION AT PURA TAMAN MUMBUL, SANGEH TRADITIONAL VILLAGE, ABIANSEMAL DISTRICT, BADUNG REGENCY - Ni Putu Ayu Wikantini; Ida Ayu Tary Puspa; Heny Perbowosari (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
The research results obtained state that the motivation of tourists visiting the Pancoran Solas Destination can be explained in terms of tourist characteristics which include socio-demographic and geographical characteristics. And the motivation of tourists to visit includes tourists' perceptions. In tourism development, all activities and businesses must be coordinated to attract tourists, especially by providing all the infrastructure, goods and services and facilities needed for tourist needs. The tourism development component consists of 6A. The implications of tourist visits include the Tri Hita Karana concept